INCREASING STUDENTS’ VOCABULARY MASTERY BY USING DISCOVERY TECHNIQUE OF X GRADE AT SMA NEGERI 2 TOLITOLI - Darwin Darwin (Jurnal Madako Education, 2019)
This research belongs to experimental design with pre-test and post-test activity. The objective of the research is to know effectifness used discovery technique to imcrease student vocabulary mastery. Sample of the research were 30 students’ of ten grade of SMA Negeri 2 Tolitoli. In doing this research, the researcher used discovey techique. The data analysis of the research was quantitative measurement to find the mean Based on the data analysis from pre-test and post-test activity. Based on the result, it was found that the use of Discovery in Teaching English is effective to increase the students’ vocabulary mastery and very beneficial for the students in order to facilitate them in Learning English. Key words: discovery, vocabulary, increasing.